Successful Myringoplasty - Do The Site & Size Of TM Perforation Matter? - Areesha Manzoor; Mirza Khizar Hameed; Irshad Ali; Nudrat Khalil; Ansa Umara; Seema Naveed (Journal of Rawalpindi Medical College)
Objective: To determine the success rate of myringoplasty based on the site and size of tympanic membrane perforation.